Recreate Tank Wheels into Rocking Chair Furniture - Yusuf, Andi Wahyu Zulkifli; Rohiman, Rohiman; Sari, Dina Mariana; Sumarsono, Adi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This research developed an innovative lounge chair design by incorporating elements of armored vehicles, specifically steel tank wheels, with merbau wood. A qualitative approach employing a creative exploration method was employed to comprehend the design engineering process and the interaction between metal and wood materials in furniture. The design process encompassed three primary stages: conceptualization, prototyping, and testing. The findings demonstrated that the steel tank wheels imparted high stability and durability, while the merbau wood enhanced aesthetic appeal and comfort. Trials of the lounge chair revealed its capacity to support substantial loads, provide ergonomic support, and offer a stable and comfortable seating experience. Additionally, the research identified challenges associated with joining metal and wood materials and the chair’s substantial weight, necessitating further design optimization. Overall, the outcomes of this study substantiate the utilization of combat vehicle materials in furniture, enhancing its functional, aesthetic, and sustainable attributes. This research contributes to the advancement of contemporary furniture design, particularly through the application of the upcycling concept to create products that possess enhanced durability and aesthetic value.